Climate information for food security in Senegal - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
In Senegal, farmers are actively using climate forecasts to stay productive and thrive under climate change. Photos taken 29-30 September in Kaffrine and Kaolack, Senegal.